PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBUDIDAYAKAN HAK ASASI MANUSIA - Ahmad Arif Fadilah; Siska Yuni Ariani; Meli Agustin (Cahaya Ilmu Bangsa Institute, 2025)
This research aims to analyze how children’s human rights are implemented, particularly in the context of access to education in Indonesia. Through case studies in several schools, this research uses qualitative observation methods and in-depth interviews with teachers and parents. The results show that there are disparities in access to education for children from different social and economic backgrounds. Factors such as tuition fees, school distance and discrimination are still obstacles in realizing children’s right to proper education. The study concludes that there is a need for more comprehensive efforts from the government, communities and schools to ensure all children can enjoy their right to quality education.